Emotional intelligence and pedagogical practice in teachers: a Scopus bibliometric study - Carhuapoma Carlos, Nelly Beatriz; Hernandez Zavaleta, Cinthia Fiorela; Ramos Fuentes, Daniel Ángel (Salud, Ciencia y Tecnología - Serie de Conferencias, 2022)
The purpose of this study was to conduct a bibliometric study in Scopus on emotional intelligence and pedagogical practice in teachers between 2008 and 2023. The research strategy was based on bibliometric analysis as a means of quantifying academic production. Sixty Scopus publications were chosen for the study based on their relevance and English keywords (emotional AND intelligence, pedagogical AND practice). The results showed that between 2018 and 2023 (n=47; 78,3 %) there was the largest increase in scientific production. In addition, one of the main sources was Advances in Intelligent Systems and Computing, while Dewaele, J.M. was the most referenced author (84 citations; 4 papers). Sixty-eight percent of the publications were research articles in the fields of social sciences (43 %), arts and humanities (14 %), and psychology (11 %). It is concluded that the thematic diversity, authorship, sources and available resources have been increasing with respect to emotional intelligence and pedagogical practice in teachers. Thus, this bibliometric analysis serves as a framework for future research by presenting documented support.